Trametinib Inhibits the Growth and Aerobic Glycolysis of Glioma Cells by Targeting the PKM2/c-Myc Axis - Gao, Mingjun; Yang, Jin; Gong, Hailong; Lin, Yuancai; Liu, Jing (Frontiers in Pharmacology, 2021)
Gliomas are primary tumors originating from glial progenitor cells. Traditional treatments, including surgery, radiotherapy, and chemotherapy, have many limitations concerning the prognosis of patients with gliomas. Therefore, it is important to find novel drugs to effectively treat gliomas. Trametinib has been shown to inhibit the MAPK pathway and regulate its downstream extracellular-related kinases. It has widely been used in the treatment of BRAF V600E mutant metastatic melanomas. Previous studies found that trametinib can improve the prognosis of patients with melanoma brain metastases. In this study, we investigated the therapeutic effects of trametinib on gliomas in vivo and in vitro. We found that trametinib can inhibit proliferation, migration, and invasion of glioma cells, while inducing apoptosis of glioma cells. Specifically, trametinib can suppress both the expression of PKM2 in glioma cells and the transport of PKM2 into the cellular nucleus via suppression of ERK1/2 expression. However, inhibition of these cellular effects and intracellular glycolysis levels were reversed by overexpressing PKM2 in glioma cells. We also found inhibition of c-myc with trametinib treatment, but its expression could be increased by overexpressing PKM2. Interestingly, when PKM2 was overexpressed but c-myc silenced, we found that the initial inhibition of cellular effects and glycolysis levels by trametinib were once again restored. These inhibitory effects were also confirmed in vivo: trametinib inhibited the growth of the transplanted glioma cell tumor, whereas PKM2 overexpression and c-myc silencing restored the inhibition of trametinib on the growth of the transplanted tumor. In conclusion, these experimental results showed that trametinib may inhibit the growth and intracellular glycolysis of glioma cells by targeting the PKM2/c-myc pathway.